WACANA MASKULINITAS DALAM VIDEO CAMPAIGN “BOYS DON’T CRY” VERSI WHITE RIBBON - Ajeng Nur Fauziah; Asrita, Stara (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2022)
Rigid construction of gender roles in society causes a bad influence on a man was toxic masculinity. Several world organizations are trying to carry out a movement to defend the issue of gender equality, one of which is the White Ribbon organization. This study uses a qualitative method with a descriptive approach. The analytical technique used is Norman Fairclough's critical discourse analysis with three dimensions, namely the text dimension, discourse practice and socio cultural practice. Researchers collect data by observation by observing the video campaign, then collect data through documentation by taking screenshots of the scene. The results show that this video campaign provides an overview of people who still practice traditional masculinity or toxic masculinity and the negative impacts that accompany it. The impact of traditional masculinity in the form of character formation that leads to a negative realm, bullying treatment and toxic masculinity. As a form of resistance to male stereotypes in this video, it is shown that it doesn't matter if men have to cry, be emotional or even hurt because they are ordinary people. The White Ribbon seeks to promote a new paradigm of healthier and more positive masculinity in the midst of labeling society.